Dread of Depreciation : Measuring Real Exchange Rate Interventions - Dutta, Jayasri (Washington, D.C. : International Monetary Fund, 2002)
We specify an empirical framework to detect the effects of official intervention on real exchange rate dynamics. Using data for 27 advanced and emerging market economies, we find evidence that interventions are a near-universal practice; almost all countries intervene when real exchange rates depreciate; interventions reduce the degree of persistence in real exchange rates; and the defense of an overvalued currency tends to be contractionary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet